KILLING LINCOLN - Campbell, Billy; Hanks, Tom; Hanks, Tom; Jendersen, Erik; Moat, Adrian; Wilson, Regen (National Geographic Channel, 2013)
Based on The New York Times best-selling novel, Killing Lincoln is the suspenseful, eye-opening story of the events surrounding the assassination of U.S. President Abraham Lincoln